Investasi dan Kemitraan untuk Energi Terbarukan dan Infrastruktur Digital - Pramarta, Pandhu; Mardiyati, Sri (Jurnal Ilmiah Global Education, 2025)
The transition toward renewable energy and the strengthening of digital infrastructure have become two critical pillars in promoting sustainable development in the modern era. Issues such as climate change, dependence on fossil fuels, and the increasing need for digital transformation require an integrated strategy involving strategic investments and cross-sector partnerships. This study aims to examine the role of investment and partnership in accelerating the development of renewable energy and digital infrastructure, focusing on the potential integration of both sectors as part of national and global development agendas. The research employs a literature review method by analyzing scientific journals, policy reports, and relevant publications that discuss trends, challenges, and opportunities in these sectors. The findings indicate a growing trend of investment in clean energy and digital systems, driven by supportive policies, private sector involvement, and technological advancements. Partnerships among governments, private companies, and research institutions have proven effective in accelerating the adoption of green and digital technologies, although challenges remain, such as digital divides, limited access to green financing, and suboptimal regulatory frameworks. This study contributes by mapping the interconnection between the two strategic sectors and providing policy recommendations based on integration frameworks. The implication is that strengthening synergy between investment and partnerships can significantly accelerate the transition to a more inclusive, efficient, and low-carbon economy, in alignment with the achievement of the Sustainable Development Goals (SDGs)